GAMBARAN PENYIMPANAN OBAT DI GUDANG OBAT INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH LAPANGAN SAWANG SITARO - Mulalinda, Rafel D.; Citraningtyas, Gayatri; Datu, Olvie S. (PHARMACON, 2020)
ABSTRACTStorage must guarantee the qualitiy and safety of pharmaceutical preperations, medical devices, and medical materials after use in accordance with pharmaceutical preparations, medical devices, and medical materials after used in accordance with pharmaceutical requirements.. The aim of this study was to evaluated the storage of medicines and to determine indicators of strengths, weaknesses, opportunities, threats that affect the storage stage in the warehouse of Pharmacy Installation of Lapangan Sawang of Sitaro District Hospital. This research was used descriptive analytical study conducted using qualitative methods. The results showed that there was 4 strength indicators, 3 weakness indicators, 1 opportunity indicator and 3 threat indicators. In conclusion, the Pharmacy Installation warehouse of Lapangan Sawang Hospital is 68% accordance with the Regulation of the Minister of Health No.72 2016, but it needs to be equipped indoor lighting, thermometers and naming (labels) on the storage rack. The warehouse strength indicators are good pharmaceutical supply management system, utilization of inventory evaluation management information systems, access to receiving goods from distributors, the person in charge of pharmaceutical personnel, the weaknesses are the number of human resources that are lacking to meet shifts, the existence of expired or damaged drugs, and have not met warehouse requirements based on the regulation. The warehouse opportunities are the development of an inventory evaluation management information system, the threat of which is the change in the inventory module, distributor regulations regarding non-returnable goods, and demand for goods or drugs during the night shift Key Word:  Storage, Medicine, Hospital Pharmacy InstallationABSTRAKPenyimpanan harus menjamin kualitas dan keamanan Sediaan Farmasi, Alat Kesehatan, dan Bahan Medis Habis Pakai sesuai dengan persyaratan kefarmasian. Tujuan dilakukan penelitian yaitu untuk mengevaluasi penyimpanan obat dan menetapkan indikator kekuatan, kelemahan, peluang, ancaman yang mempengaruhi tahap penyimpanan  di gudang Instalasi Farmasi Rumah Sakit (IFRS) Umum Daerah Lapangan Sawang Sitaro. Penelitian ini merupakan penelitian deskriptif analitis yang dilakukan dengan metode kualitatif. Hasil penelitian menunjukkan terdapat 4 indikator kekuatan, 3 indikator kelemahan, 1 indikator peluang dan 3 indikator ancaman. Kesimpulannya gudang IFRS Umum Daerah Lapangan Sawang 68% sesuai dengan Peraturan Menteri Kesehatan (PMK) No.72 Tahun 2016, namun perlu untuk dilengkapi penerangan dalam ruangan, termometer dan penamaan (label) pada rak penyimpanan. Indikator kekuatannya ialah sistem penataan perbekalan farmasi yang baik, pemanfaatan sistem informasi manajemen evaluasi inventory, akses penerimaan barang dari distributor, penanggung jawab dari tenaga kefarmasian, kelemahannya yaitu kurangnya jumlah SDM untuk memenuhi shift, adanya obat kadaluarsa/rusak, dan belum memenuhi persyaratan gudang berdasarkan PMK. Peluangnya ialah perkembangan sistem informasi manajemen evaluasi inventory, ancamannya yaitu perubahan modul inventory, peraturan distributor barang yang tidak dapat diretur, dan permintaan barang/obat saat shift malam. Kata Kunci: Penyimpanan, Obat, Instalasi Farmasi Rumah Sakit